2016
DOI: 10.3390/sym8100099
|View full text |Cite
|
Sign up to set email alerts
|

Structural Distortion Stabilizing the Antiferromagnetic and Semiconducting Ground State of BaMn2As2

Abstract: Abstract:We report evidence that the experimentally found antiferromagnetic structure as well as the semiconducting ground state of BaMn 2 As 2 are caused by optimally-localized Wannier states of special symmetry existing at the Fermi level of BaMn 2 As 2 . In addition, we find that a (small) tetragonal distortion of the crystal is required to stabilize the antiferromagnetic semiconducting state. To our knowledge, this distortion has not yet been established experimentally.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
(122 reference statements)
2
10
0
Order By: Relevance
“…Because NiO is a prototype Mott insulator [5,6,21], the magnetic super band of NiO is evidently half filled, and the Mott condition is evidently satisfied in this band. As mentioned, I already found a magnetic super band in the band structure of BaMn 2 As 2 [17]. In fact, also BaMn 2 As 2 is a band gap insulator, often referred to as a small band gap semiconductor [22,23].…”
Section: Mott Insulator: Third Condition Of Stabilitymentioning
confidence: 80%
See 4 more Smart Citations
“…Because NiO is a prototype Mott insulator [5,6,21], the magnetic super band of NiO is evidently half filled, and the Mott condition is evidently satisfied in this band. As mentioned, I already found a magnetic super band in the band structure of BaMn 2 As 2 [17]. In fact, also BaMn 2 As 2 is a band gap insulator, often referred to as a small band gap semiconductor [22,23].…”
Section: Mott Insulator: Third Condition Of Stabilitymentioning
confidence: 80%
“…The results of this paper corroborate that the nonadiabatic atomic-like motion defined within the NHM is physically existent if the considered metal possesses a narrow, partly filled band with suitable Wannier functions (Section 5.1). The success in the last 40 years in identifying narrow, roughly half filled superconducting [9,27] and magnetic [9,17] bands in the conventional band structures of superconducting and magnetic materials provides evidence that the nonadiabatic atomic-like motion as defined in the NHM actually has physical reality and stabilizes the superconducting and magnetic states, respectively, in these materials. In addition, our results on NiO and BaMn 2 As 2 [17] suggested that "magnetic super bands" (Section 6) may stabilize insulating ground states in a magnetic phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations